Erratum to: “EPR Spectroscopy of Tetraborate Glasses, Doped with Mn and Cu”, CTBo 2010, 33 (Suppl. A) 171-175 - Padlyak, Bohdan V.; Drzewiecki, Adam; Smyrnov, Oleksandr O. (Current Topics in Biophysics, 2014)
[Missing]